Fresh off the boat. The complete second season [videorecording (DVD)] - Shelton, Lynn; Scanlon, Claire; Park, Randall; Wu, Constance, 1982-; Yang, Hudson, 2003-; Huang, Eddie, 1982- (Twentieth Century Fox Home Entertainment, 2018)
Follows the adventures of a Taiwanese family newly immigrated to the United States in the 1990s.